Taxonomic synopsis of Brassicaceae for the flora of Jordan. Issue 2 (2nd July 2016) - Al-Eisawi, Dawud
Abstract : The family Brassicaceae in Jordan is revised based on the latest evidence and latest taxonomic information. The family Brassicaceae was included in the country's first checklist for vascular plants in 1982, and more recently in 2013. The present study presents all accepted species (137) and genera (66) according to their tribal affiliations. Accordingly, this study shows that ten previously accepted genera are excluded from the checklist for Jordan. Eleven new genera have been established and are represented in the flora of Jordan, which reflects substantial taxonomic investigation and change.